The effects of neuroinflammation induced by systemic lipopolysaccharides on the hippocampi of aged Sprague-Dawley rats - Bester, Janette (University of Pretoria, 2022)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2022.